2022
DOI: 10.1186/s13018-022-02956-2
|View full text |Cite
|
Sign up to set email alerts
|

The validity and accuracy of 3D-printed patient-specific instruments for high tibial osteotomy: a cadaveric study

Abstract: Objective High tibial osteotomy (HTO) has been used for the treatment of patients with knee osteoarthritis. However, the successful implementation of HTO requires precise intraoperative positioning, which places greater requirements on the surgeon. In this study, we aimed to design a new kind of 3D-printed patient-specific instrument (PSI) for HTO, including a positioning device and an angle bracing spacer, and verify its effectiveness using cadaveric specimens. M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…The authors concluded about a high accuracy of the system, with Pearson's correlation coefficient values similar to those obtained in this study [14]. Miao et al evaluated the accuracy of an angular spacer on 8 specimens, with no significant differences in planned and post-operative MPTA [17]. However, CT scan measurements were performed separately and not superimposed, which may induce doubts in the validity of the comparison.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The authors concluded about a high accuracy of the system, with Pearson's correlation coefficient values similar to those obtained in this study [14]. Miao et al evaluated the accuracy of an angular spacer on 8 specimens, with no significant differences in planned and post-operative MPTA [17]. However, CT scan measurements were performed separately and not superimposed, which may induce doubts in the validity of the comparison.…”
Section: Discussionsupporting
confidence: 78%
“…Recently 3D patient-specific cutting guides (PSCG) based on Computer Tomography (CT) scans were developed. Preliminary in vitro studies described very good accuracy for some PSCG systems on both the coronal and sagittal plane [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…An additional study was excluded because it investigated the osteotomy procedure to correct tibial plateau fractures’ non-union [ 12 ]. A total of 28 articles [ 6 , 7 , 8 , 9 , 10 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ] were included in this systematic review ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cadaveric studies investigating the accuracy of patient-specific 3D-printed device for HTO have risen in recent years [ 8 , 9 , 15 , 26 ], reporting a mean difference between planned and achieved medial proximal tibial angle (MPTA) under 1° ( Table 3 ). These favorable results have also been confirmed in in vivo studies ( Table 2 a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation